The Feasibility of English Textbook for Vocational School - Masrupi Masrupi; Akhmad Baihaqi; Miftahul Hakim (Journal of English Language Teaching and Cultural Studies, 2020)
The objective of the research is aiming to identify the feasibility of the English textbooks for use by vocational school in Pandeglang regency. To reach the objective, the researchers used qualitative research. The data were collected from three English textbooks used for vocational school, interview, and questionnaire. The techniques of analyzing data were focused on the analysis of materials provided within the textbook with the core and basic competence of 2013 curriculum. The criteria were suggested by National Education Standards Agency (Badan Standar Nasional Pendidikan) and Rajan material design. The findings show that (1) the material relevance to the core and basic competence of 2013 Curriculum of the first English textbook (TB1) is 81.25%, the second English textbook (TB2) is 93.75%, and the third English textbook (TB3) is 87.5%; and (2) the categories of feasible textbook for vocational students for TB1 is 83.3%, TB2 is 91.6%, and TB3 is 75%. These results indicate that the three books are relevant and feasible for use by vocational school students.